Poverty Alleviation through Zakat and Income Distribution on Agriculture of Local Commodity, Honey Pinneapple, in Pemalang Regency - Indin Rarasati & Diah Setyawati Dewanti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research has an aim to study the comparation fron level of income distribution andpoverty index before and after the Zakat on agriculture applied in Beluk village,Pemalang regency. Beluk village supply high quality local pinneaple fruits in Indonesiaand brought pinneaple to improve the income and alleviate the proverty of pinneaplefarmers. As common people know, zakat can distribute the income of Muslim equally.Neverthless, Zakat as an instrument in Islamic able to alleviate the poverty. This researchuse of purposive random sampling in order to get 100 people as sample size. Therespondents consist of honey pineapple local farmers who live in Desa Beluk and localpeople of Desa Beluk as non-farmer. In order to know the level of inequality from incomedistribution, the research measured Gini Index, Lorenz curve, and World Bank’s criteriaas the tool to gain the research objective. In order to know the level of poverty, this studyuse FGT index to measure headcount ratio, poverty gap index, and poverty severity indexas the tool of analyzing. Through the system of income distribution as the legal principlein Islamic economics, Zakat on agriculture decrease the level of inequality as Gini Index0.45 and causes the income the distribution on Desa Beluk more equal after the Zakat ofagriculture enacted. To recognize the level of poverty in terms of proportion, depth andseverity of poverty, this study measured FGT index through head count ratio, poverty gapindex, and poverty severity index. It shows decreasing index after the zakat on agriculturemeasured which proof Zakat on agriculture is directly reduce the poverty index. The headcount ratio is decrease 0.01, povery gap index decrease as 0.08 and poverty severity indexdecrease as 0.298.Keywords: Zakat on agricultural, Inequality, Distribution of Income, Poverty, Beluk village